Intraoperative management of combined general anesthesia and thoracic epidural analgesia: A survey among German anesthetists. Issue 10 (5th September 2021) - Schlesinger, Tobias; Weibel, Stephanie; Steinfeldt, Thorsten; Sitter, Magdalena; Meybohm, Patrick; Kranke, Peter
Abstract: Background: Evidence concerning combined general anesthesia (GA) and thoracic epidural analgesia (EA) is controversial and the procedure appears heterogeneous in clinical implementation. We aimed to gain an overview of different approaches and to unveil a suspected heterogeneity concerning the intraoperative management of combined GA and EA. Methods: This was an anonymous survey among Members of the Scientific working group for regional anesthesia within the German Society of Anaesthesiology and Intensive Care Medicine (DGAI) conducted from February 2020 to August 2020. Results: The response rate was 38%. The majority of participants were experienced anesthetists with high expertise for the specific regimen of combined GA and EA. Most participants establish EA in the sitting position (94%), prefer early epidural initiation (prior to skin incision: 80%; intraoperative: 14%) and administer ropivacaine (89%) in rather low concentrations (0.2%: 45%; 0.375%: 30%; 0.75%: 15%) mostly with an opioid (84%) in a bolus‐based mode (95%). The majority reduce systemic opioid doses intraoperatively if EA works sufficiently (minimal systemic opioids: 58%; analgesia exclusively via EA: 34%). About 85% manage intraoperative EA insufficiency with systemic opioids, 52% try to escalate EA, and only 25% use non‐opioids, e.g. intravenous ketamine or lidocaine. Conclusions: Although, consensus seems to be present for several aspects (patient's position during epidural puncture, main epidural substance, application mode), there is considerable heterogeneity regarding systemic opioids, rescue strategies for insufficient EA, and hemodynamic management, which might explain inconsistent results of previous trials and meta‐analyses.